Independent evaluation of tolerance of therapeutic plasma inactivated by amotosalen‐HCl–UVA (Intercept™) over a 5‐year period of extensive delivery. Issue 4 (29th May 2015) - Bost, V.; Chavarin, P.; Boussoulade, F.; Fabrigli, P.; Chabre, C.; Benamara, H.; Odent‐Malaure, H.; Legrand, D.; Cognasse, F.; Garraud, O.
<x xml:space="preserve">Abstract</x> Amotosalen‐HCl–UVA (AI) is a process to inactivate pathogens in therapeutic plasma (FFP). Tolerance is the main residual issue in FFP transfusion, and only large series observations are powered enough to identify significantly elevated levels of hazards. We report here on 15 133 new transfusions of AI‐FFP, over the previously published 36 035, which in all represents one of the largest series observed by means of a highly standardized surveillance (51 168 observations). There is no noticeable difference in terms of tolerance of AI‐FFP compared to 5875 transfusions of Quarantine (Q)‐FFP. There was no significant difference in terms of advance events, between the two types of FFP (P = 0·98); further, no difference was recorded either when the total number of AI‐FFP (51 168) was compared to the corresponding number of Q‐FFP (5875; P = 0·62).